DIFFERENT APPROACHES TO THE DEFINITION OF THE CONCEPT "INFORMATION CULTURE" IN SCIENTIFIC LITERATURE - O.V. Hanchuk (Academy of Cognitive and Natural Sciences, 2004)
The different methodological approaches for définition of the essence of the notion information culture are analyzed. The author gives his own définition of the sociocultural phenomenon.